How does cultural capital influence the school choice of rural and urban migrant families in Nanjing, China? Evidence from a survey study - Yang, Liuning (Australian and International Journal of Rural Education, 2022)
Across China, the household registration (hukou) policy has restricted the school admission of rural–urban migrant children in urban areas. In 2017, the Nanjing government issued the Tenants Have the Same Right as Householders (THSRH) policy to allow tenants in urban areas access to public-school resources. However, what the migrant children have experienced in and after negotiating access to these schools deserves serious attention from educators, scholars and policymakers. This study surveyed 186 rural–urban migrant parents in Nanjing who chose to send their children to junior secondary schools after the implementation of the THSRH policy. The study identified that higher socioeconomic and household status of rural–urban migrants increased their choices for junior secondary schools. However, the study demonstrated that the restriction in the hukou policy is still a dominant factor influencing public-school access. The study highlighted that the interaction of the development of extracurricular abilities and investment in private supplementary tutoring are two main factors that influence the school choices of rural–urban migrant families.